Teacher morale and other variables as correlates of student achievement in first year mathematics in MECS, Region II - Tajon, Angeles F. (Fres) 1930- (1985)
This study was conducted among 93 first year secondary mathematics teachers in the public and private high schools in Region 2 in 1984-1985 and 1,860 of their students who were given the MECS achievement test for first year mathematics. Public school teachers had higher morale with respect to the role of the supervisors and his readiness to help teachers, uniform allowance, and administrators' relationship with teachers. Private school teachers scored higher on the adequacy of facilities and equipment, textbooks and references, furnishing of classrooms, table armchairs, laboratory rooms and availability of faculty room. Student achievement in the region, which is higher than the national class mean achievement, is not significantly related to teacher morale but school type and sex of teacher are negatively related to student achievement.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Keywords: Mathematics teachers -- Philippines -- Cagayan Valley; Mathematics -- Study and teaching (Secondary) -- Philippines -- Cagayan Valley